KELUARGA 5.0: DINAMIKA PENGGUNAAN TEKNOLOGI DALAM RELASI SOSIAL KELUARGA MODERN - Fathiyah; Vionita, Fani (SHOUTIKA, 2025)
This study explores the dynamics of modern families in the context of digital technology development. Using a literature review method, the research synthesizes findings from various interdisciplinary studies on family communication, digital literacy, and the influence of social media. The findings reveal that although technology increases the frequency of family interactions, the quality of emotional closeness may decline. Key concerns include intergenerational gaps in digital literacy, parental digital surveillance, and issues of privacy and performativity on social media. Adaptive strategies such as open communication, digital literacy training, and participatory technology policies can strengthen family cohesion. This study also highlights the need for integrating communication and technology theories to understand digital family life. Theoretical and practical implications, along with directions for future research, are discussed to support digitally resilient families.